P420 Comparative efficacy and safety of oral ferric maltol in Inflammatory Bowel Disease patients with mild-to-moderate vs. more severe iron deficiency anaemia. (27th May 2021) - Akriche, F; Jacob, I; Schmidt, C; Howaldt, S
Abstract: Background: The efficacy and safety of ferric maltol (FM) has been demonstrated in inflammatory bowel disease (IBD) patients with mild-to-moderate iron deficiency anaemia (IDA; haemoglobin [Hb] ≥ 9.5 g/dL). New data are available from a recent open-label, Phase 3b non-inferiority study comparing the efficacy and safety of FM to ferric carboxymaltose for IBD patients with more severe IDA (Hb at screening: 8.0 - 11.0/12.0 g/dL [women/men]) (NCT02680756). Though the primary endpoint was not met, this post hoc analysis aimed to utilise patient-level data to confirm the efficacy and safety of FM in patients with baseline Hb < 9.5 g/dL. Methods: Patients assigned to FM (N=125) were grouped based on baseline Hb: <9.5 g/dL (n=38) and ≥9.5 g/dL (n=87). Univariate and multivariate analyses were performed for primary (Week 12 change from baseline [CFB] Hb) and key secondary endpoints (Week 12 responder rate [≥2 g/dL Hb increase or Hb normalisation] and long-term efficacy). Safety analysis was performed. Results: Overall, demographic characteristics were broadly comparable with a greater, but not significant, proportion of females (63.2% vs. 50.6%), women of childbearing age (75.0% vs. 63.6%) and active Crohn's disease (37.5% vs. 32.7%) in patients with baseline Hb < 9.5 g/dL vs. ≥ 9.5 g/dL, respectively. Mean baseline Hb was 8.6 g/dL in patients with baseline Hb < 9.5 g/dL and 10.6 g/dL in patients with baseline Hb ≥ 9.5 g/dL. There was no significant difference in mean CFB Hb at Week 12 (2.92 g/dL vs. 2.35 g/dL, p=0.960) and Week 12 responder rates (70.0% vs. 67.1%, p=0.523) in patients with baseline Hb < 9.5 g/dL and ≥ 9.5 g/dL, respectively. Mean CFB Hb was numerically but not significantly higher in patients with baseline Hb < 9.5 g/dL at every visit up to Week 52 (Table 1). Drug-related treatment emergent adverse events were similar between < 9.5 g/dL and ≥ 9.5 g/dL Hb groups (15.8% vs. 21.3%, respectively); all non-serious. Conclusion: FM achieved consistent and clinically meaningful increases in Hb in patients with baseline Hb < 9.5 g/dL that were comparable to patients with Hb ≥ 9.5 g/dL. No safety differences were identified between both groups. These data suggest that FM is effective and well tolerated in IBD patients with IDA regardless of baseline Hb.